Expression and biological significance of human kallikrein 6 in gastric cancer tissues - Hu, Cheng Jin; Chen, Kui Xiang; Zheng, Jin Feng; Chen, Ying Jian (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study: This study aims to investigate the expression of human kallikrein 6 (hK6) in gastric cancer, gastric ulcer and normal gastric mucosa tissues and its biological significance. Material and methods: The expression of hK6 in 15 normal gastric mucosa (NGM) tissues, 15 gastric ulcer (GU) tissues and 55 gastric carcinoma (GC) tissues was respectively detected by immunohistochemistry. The correlations between the expression of hK6 and the clinical pathological parameters of gastric cancer were also analyzed. Results: Human kallikrein 6 was mainly expressed in cytoplasm. The positive rate of hK6 was significantly higher in gastric cancer tissues than that in gastric ulcer or normal gastric mucosa tissues (70.9%, 40% and 20%, respectively, p < 0.01). With the increase of the invasion depth of gastric cancer cells, aggravation of TNM stage and development of lymph node metastasis, the expression of hK6 increased significantly (p < 0.05 and p 0.05). Conclusions : The overexpression of hK6 is related to the depth of invasion, lymph node metastasis and clinical stage of gastric carcinoma, which suggests that hK6 may act as a new marker of gastric cancer biological behavior.